An Ecological Overview of Red Panda - Adhikari, Arun (The Initiation, 2010)
According to recent report, 20% of world's wild mammals are threatened with extinction. One of them, Red panda is also in the front list. Decreasing number of Red Panda compells us to think about all its related activities and our role to conserve it. Habitat destruction is one of the main cause of its reducing number. So, we need to keep in mind about its characteristics and requirements, seriously. This article is trying to provide imformation about present status of Red Panda which gives a way forward for its better management. Researches on Red Panda are found in very limited numbers in Nepal. This article is written to promote the research on this species intensively which can help in biodiversity conservation from our side. Key Words: Red Panda, Bamboo, Solitary, Threatened, Behavior, Habitat, Conservation DOI: 10.3126/init.v3i0.2506 The Initiation Vol.3 2009 p.149-152